Citra Perusahaan Asuransi Kredit Modal Kerja di Jawa Barat - Nasir, Amron Ahmad (JURNAL PENELITIAN EKONOMI DAN BISNIS, 2013)
this research is aimed to analyze and to know influence significan of performance promotion program decision to working capital credit insurance company image in West Java, Indonesia.